Online Mindfulness Intervention, Mental Health and Attentional Abilities: A Randomized Controlled Trial in University Students During COVID-19 Lockdown - Devillers-Réolon, Louise; Mascret, Nicolas; Sleimen-Malkoun, Rita (Frontiers in Psychology, 2022)
The COVID-19 pandemic has led to worldwide restrictive measures, raising concerns about mental health in young adults who were not particularly vulnerable to the virus itself. This study investigated the impact of these restrictions on mental and cognitive health of university students, and tested the efficacy of a brief online mindfulness meditation intervention in countering psychological distress and improving attentional abilities. Ninety-six university students forced into remote learning due to COVID-19 pandemic restrictions and with no experience in meditation were randomly assigned to either a passive control group (N=48) or to an experimental group (N=48) following daily, for 17 days, an online mindfulness intervention (10-20 minutes per day). Due to drop-out, 38 participants in each group were finally analyzed. Pre- and post-tests assessed participants’ mental health (psychological well-being, depression, anxiety, stress) and attentional abilities. The analysis of baseline data in comparison to normative scores and pre-pandemic statistics confirmed the expected psychological distress, but it did not reveal any attentional deficits in our participants. Pre-post change scores analyses showed a reduction in stress (p = .006, p2 = .10), anxiety (p =.002, p2 = .13), and depression (p = .025, p2 = .07), and an improvement in well-being (p = .013, p2 = .12) in the experimental group, but not in the control group. In both groups, no significant effect was found on attentional abilities. Our results confirmed the psychological vulnerability of higher education students in the midst of the remote learning period during the second COVID-19 lockdown in France, while suggesting preservation of attentional functioning. Although the tested mindfulness intervention did not enhance the attentional abilities in already good performing students, it did promote their mental health. This study offers additional evidence on the feasibility and efficacy of mindfulness-based interventions in students during psychologically straining periods, like the COVID-19 pandemic.